177 An unusual presentation in motor neurone disease. Issue 9 (12th August 2022) - Terry, Robyn; Tanti, Matthew; Jung, Agam; Mavroudis, Ioannis; Devinuwara, Kanch; Sivakumar, Gnanamurthy
Abstract : Motor Neurone Disease (MND) is a life limiting neurodegenerative condition. Spasticity in MND is usually managed with oral medications. Intrathecal baclofen (ITB) is occasionally used. While there is some expe- rience of ITB in Primary Lateral Sclerosis (PLS) there are few reports of ITB in the context of Amyotrophic Lateral Sclerosis (ALS). Paroxysmal sympathetic hyperactivity (PSH) is known to occur with central nervous system (CNS) insults, but there is only one prior reported case of MND with PSH in the literature. We report a patient with an eight-year history of PLS, sleep apnoea, recent immobility and conversion to ALS who developed PSH after ITB pump insertion. His spasticity was severe despite oral medications and the ITB insertion resulted in dramatic improvement. Two months post procedure he developed recurrent episodes of facial flushing, hypertension, tachycardia and headache, typical of PSH, which seemed to follow episodes of sleep apnoea. Other somatovisceral triggers were not found. Imaging of the neuraxis revealed peri-rolandic atrophy in keeping with ALS but no new CNS lesions. PSH in our patient seemed to follow ITB insertion despite ITB being a treatment for PSH. More studies are required to assess efficacy and complications of ITB for patients with MND.